Generic and Indexed Programming - Gibbons, J; Wang, M; Oliveira, B (2007)
The EPSRC-funded Generic and Indexed Programming project will explore the interaction between datatype-generic programming (DGP) — programs parametrized by the shape of their data — and indexed programming (IP) — lightweight dependently-typed programming, with programs indexed by type-level representations of properties. Integrating these two notions will provide new ways for programmers to capture abstractions.